Divine inspirations: music and Islam in Indonesia - Harnish, David D.; Rasmussen, Anne K. (Oxford University Press, 2011)
From the rhythmic grooves of dang dut, the archipelago's tenacious pop music, to the oft-quoted image of the wayang shadow puppet-theater, this book investigates the expression of the Muslim religion through a diversity of art forms in this region.